Persistence and compliance with medication management in the treatment of overactive bladder - Kim, Tae Heon (Investig Clin Urol, 2016)
Overactive bladder (OAB) is a common and chronic condition that impacts patients' daily activities and quality of life. Pharmaco-therapy for OAB is a mainstay of treatment. Antimuscarinics and β3-adrenoceptor agonists are the two major classes of oral pharmacotherapy and have similar efficacy for treating the symptoms of OAB. Owing to the chronic nature of OAB, long-term use of medication is essential for OAB symptom control and positive health outcomes. However, many patients elect to stop their medications during the treatment period. Unmet expectations of treatment and side effects seem to be the major factors for discontinuing OAB pharmacotherapy. Furthermore, the short- and long-term persistence and compliance with medication management are markedly worse in OAB than in other chronic medical conditions. Improvement in persistence and compliance with OAB pharmacotherapy is a hot topic in OAB treatment and should be an important goal in the treatment of OAB. Effective strategies should be identified to improve persistence and compliance. In this review, we outline what is known about persistence and compliance and the factors affecting persistence with pharmacotherapy in patients with OAB.